Analisis Kualitas Air Laut dan Implikasinya terhadap Produktivitas Perikanan di Pesisir Indonesia - Ahmad Pratama; Siti Rahmawati (Journal of Marine Fisheries, 2025)
This study analyzes the quality of seawater and its implications for fisheries productivity along the Indonesian coast. Coastal ecosystems are highly dependent on water quality, which influences the sustainability of fish populations and community livelihoods. The purpose of this research is to assess key water quality parameters such as temperature, salinity, pH, dissolved oxygen, and nutrient concentration, and evaluate their relationship with fishery yields. The study employed a mixed-method approach, combining field measurements with secondary data analysis from environmental and fisheries institutions. Results indicate that declining water quality, particularly due to eutrophication and heavy metal pollution, has significantly reduced fish diversity and productivity in several regions. Conversely, areas with stable environmental conditions exhibited higher fisheries productivity. The findings suggest the urgent need for integrated coastal management policies to ensure sustainable fisheries. This research contributes to a better understanding of the link between marine environmental health and fisheries productivity, providing valuable insights for policymakers, researchers, and local communities.